Malakoplakia and xanthogranulomatous pyelonephritis treated with nephrectomy: A case report. Issue 36 (10th September 2021) - Pan, Yueh; Hong, Ying Chui; Shih, Hung-Jen; Chang, Chin-Pao; Huang, Sheng-Hsien; Wu, Sheng-Chuan; Lee, Liang-Ming; Wen, Yu-Ching; Hsu, Chih-Chen; Hsiao, Chi-Hao
Abstract: Rationale: Malakoplakia and xanthogranulomatous pyelonephritis are chronic inflammatory conditions of the kidney characterized by the infiltration of inflammatory cells. Patient concerns: An 82-year-old female patient had a history of hypertension, type 2 diabetes mellitus, dyslipidemia, and end-stage renal disease under hemodialysis. She was admitted repeatedly 4 times within 4 months due to urosepsis. Diagnosis: The enlarged right kidney with a low-density lesion at the right middle calyx, and a well-enhanced ureter were noted on the computed tomography scan. Therefore, xanthogranulomatous inflammation was suspected. Semi-rigid ureteroscopy with biopsy was performed, and xanthogranulomatous inflammation of the ureter was confirmed on the pathology report. Interventions: After right open radical nephrectomy was performed, the final pathology report revealed malakoplakia with xanthogranulomatous pyelonephritis. Outcomes: After the surgery, she has no longer suffered from urosepsis for 8 months, and there were no adverse event or recurrence noted. Lessons: With this case report, we aim to emphasize that these 2 diseases are not mutually exclusive, but they may exist simultaneously in the same patient.